Time hopping short reference carrier index differential chaos shift keying communication scheme - Hua YANG; Yu WANG; Siyuan XU; Guoping JIANG (Tongxin xuebao)
In order to effectively utilize the transmission power of the reference signals in carrier index differential chaos shift keying (CI-DCSK), a novel time hopping short reference carrier index differential chaos shift keying communication system was proposed.Firstly, the symbol time was divided into multiple time slots, one of which was selected to send short reference signals according to the reference index bits.Then, analytical bit error rate expressions over additive white Gaussian noise and multipath Rayleigh fading channels were derived.Simulation results verify that the proposed scheme has a significant improvement in spectral efficiency, system energy efficiency and bit error rate performance.